Early cerebral hemodynamic, metabolic and histological changes in hypoxic-ischemic fetal lambs during postnatal life - Rey-Santano, Carmen; Mielgo, Victoria E.; Murgia, Xabier; Gastiasoro, Elena; Lafuente, Hector; Ruiz-del-Yerro, Estibaliz; Valls I Soler, Adolf; Hilario, Enrique; Alvarez, Francisco J. (Frontiers in Neuroscience, 2011)
The hemodynamic, metabolic and biochemical changes produce during transition from fetal to neonatal life could be aggravated if asphyctic event occur during fetal life. The aim of the study was to examine the regional cerebral blood flow (RCBF), histological changes, and cerebral brain metabolism in preterm lambs, and to analyze the role of oxidative stress for the first hours of postnatal life following severe fetal asphyxia. 18 chronically instrumented fetal lambs were assigned to: hypoxic-ischemic group, following fetal asphyxia animals were delivered and maintained on intermittent-positive-pressure-ventilation for 3 hours, and non-injured animals that were managed similarly to the previous group and used as control group. During hypoxic-ischemic insult, injured group developed acidosis, hypoxia, hypercapnia, latacidaemia and tachycardia in comparison to control group, without hypotension. Intermittent-positive-pressure-ventilation transiently improved gas exchange and cardiovascular parameters. After HI injury and during ventilation-support, the increased RCBF in inner zones was maintained for hypoxic-ischemic group, but cortical flow did not exhibit differences compared to the control group. Also, the increase of TUNEL positive cells (apoptosis) and antioxidant enzymes, and decrease of ATP reserves was significantly higher in the brain regions where the RCBF were not increased. In conclusion, early metabolic, histological and hemodynamic changes involved in brain damage have been intensively investigated and reported in premature asphyctic lambs for the first 3 hours of postnatal life. Those changes have been described in human neonates, so our model could be useful to test the security and the effectiveness of different neuroprotective or ventilatory strategies when are applied in the first hours after fetal hypoxic-ischemic injury.